Pendidikan Kewarganegaraan Dalam Membangun Karakter Bangsa Di Era Digital - Zebua, Hertini; Halawa, Eduardus Heronimus (CV. SINAR HOWUHOWU, 2025)
Abstract Civic Education (PKn) plays a crucial role in shaping the nation's character, especially in facing the challenges and opportunities presented by the digital era. PKn aims to equip students with an understanding of their rights and duties as citizens, as well as instill national values based on Pancasila and the 1945 Constitution. In the digital era, technological advancements provide easier access to information but also pose a challenge in preserving national values often eroded by the global information flow. Therefore, civic education must be adjusted to technological developments, accompanied by the enhancement of critical thinking and empathy skills. Technology-based learning strategies, such as the use of digital media and social platforms, can make the learning process more engaging and relevant to the younger generation. This study aims to examine the role of PKn in building the nation's character in the digital age and strategies that can be implemented to optimize PKn learning.